Kedudukan Ombudsman Dan Kepatuhan Penyelenggara Negara Dalam Melaksanakan Rekomendasi Ombudsman (Study OMBUDSMAN Perwakilan Maluku Utara) - Sukitman Asgar; Sahrestia Kartianti (Wajah Hukum, 2022)
The Ombudsman is one of the state agencies authorized to oversee public services in Indonesia based on the provisions of law number 37 of 2008. Therefore, this study aims to examine the position of the Ombudsman in the perspective of Constitutional Law as an external government supervisory agency and to determine the compliance of state administrators in carry out the recommendations of the Ombudsman Representative of North Maluku Province. To obtain accurate research results, a good and correct flow and method is needed, so this research was carried out using a normative empirical research type which was analyzed in a juridical perspective based on statutory provisions and observed directly in the field in order to determine the existence and existence of the Ombudsman as an institution. External Supervisors as well as the effectiveness of the implementation of the law and the compliance of the State Organizers on the Recommendations issued by the North Maluku Ombudsman. After conducting the study and analysis results, it was found that the existence of the Ombudsman is very necessary to avoid and prevent the Corrupt Behavior of state administrators and in order to maintain the constitutional rights of citizens to get good and excellent service, it's just that there needs to be an expansion of authority by forwarding the findings to the public. repressive law enforcement agencies. Another thing is the low propriety of state officials against the recommendations of the Ombudsman due to the absence of strict sanctions. On the other hand, the authority of the Central Ombudsman does not apply mutandically in regions that can only issue suggestions and opinions that differ from the Central Ombudsman who is authorized to issue recommendations.